Salinity Reduction from Poly-Chem-Industrial Wastewater by Using Microalgae (Chlorella sp.) Collected From Coastal Region of Peninsular Malaysia - Bhuyar, P.; Hong, Dang Diem; Mandia, Emelina; Mohd Hasbi, Ab. Rahim; Gaanty Pragas, Maniam; Govindan, Natanamurugaraj (Gnoscience Group, 2020)
The potential of microalgae as a source of bioremediation based on wastewater has received increasing interest throughout the world. A freshwater microalga Chlorella vulgaris was investigated for its ability to reduce salinity from six different polychem industrial wastewaters which were diluted in microalgae in three different proportions (namely, 1:6, 1:1 and 2:1). The results reveled that C. vulgaris grew in wastewater of chemical and fertilizer company, obtained value of pH, salinity, DO, salinity and TDS did not change while absorbance value decreased from day 0 to day 30 due to highly acidic nature. For polymer, dye, RO, and petroleum industry wastewater, the absorbance and pH value increase for all concentration. The lowest salinity and TDS for poly, dye, RO and petroleum industry were all at the concentration of 2:1. The result showed that, Chlorella sp. managed to reduce the salinity for wastewater polymer, dye, RO, and petroleum industry, at concentration of 2:1 which were 3.67 %, 4.53 %, 5.4 %, and 4.91 % respectively. The results suggest that the potential of removing nutrient from wastewater by microalgae cultivation as production feedstock.